Penyuluhan Pemanfaatan Lahan Pekarangan Sebagai Kawasan Rumah Pangan Lestari (KRPL) di Kampung Asei Kecil, Sentani Timur Kabupaten Jayapura - Warpur, Maklon; Manalu, Khristhoper Aris Arianto; Ayer, Popi Ida Laila; Mantayborbir, Vyona (Jurusan Biologi FMIPA Universitas Cenderawasih, 2024)
Socialization about the use of yard land as a sustainable food home area in Asei Kecil Village, East Sentani District, Jayapura Regency, it was held on May 30 2023. This activity aims to provide motivation and understanding to the community about the importance of using yard land as a sustainable food home area) to support family food security. The methods used in this activity are lectures, discussions and questions and answers. This activity successfully involved 23 participants. The implementation of outreach activities regarding the use of yard land as a sustainable food area began with an introduction to the team and continued with a speech from the head of Asei Kecil Village, followed by the provision of materials. The team's presentation of material began with an explanation of the benefits of managing a home yard as a sustainable food area. The participants were very enthusiastic about following the presentation of the material, this could be seen from several questions asked regarding the material provided in the question and answer and discussion session. Based on the results of the evaluation carried out by the team using a questionnaire measuring tool, it showed that 78.20% of respondents agreed that the socialization on the use of yard land as a sustainable food house area was interesting and easy to understand, then 65.22% of respondents agreed that the socialization on the use of yard land provided by the team community service provides new experiences regarding the use of yard land as a sustainable food house area.